Seasonal and interannual coastal wind variability off the central Maluku Islands revealed by satellite oceanography - Setiawan, R. Y.; Iskandar, I.; Wirasatriya, A.; Dwi Susanto, R.; Siswanto, E.; Pranowo, W .S.; Setiawati, M. D.; Mardiansyah, W. (Global NEST, 2022)
The Maluku Islands (henceforth MI) are situated in the northeastern Indonesia. Ocean region off the central MI is pivotal as it provides a course for the Indonesian Throughflow (ITF) through the Lifamatola passage. However, sea surface dynamics off the central MI is unknown until recently due to inadequate measurements. The current fact motivates the present study to decipher the coastal wind variability off the central MI and its effect on the sea surface by analysing long-term datasets (2007-2019) of satellite-derived sea surface wind, sea surface temperature (SST), and surface chlorophyll-a concentration. Possible influence of extreme climate events of the 2015 El Niño-Southern Oscillation (ENSO) and the 2019 Indian Ocean Dipole (IOD) on all oceanographic parameters was also examined. Results show that the prevailing southeasterly winds over the central MI induce SST cooling and phytoplankton bloom. Correlation analysis revealed that the ENSO and IOD play significant roles in defining spatial distribution of the coastal wind, SST, and phytoplankton bloom in the research area. In addition, the anomaly analysis exhibits distinct oceanographic features during the climate extreme events of 2015 and 2019. Collectively, results of the present research highlight the importance of coastal wind variability and extreme events in shaping the ocean surface characteristics and perhaps regional fisheries production. © 2022 Global NEST.